Show that


$y=x^{2}+2 x+\mathrm{C} \quad: y^{\prime}-2 x-2=0$


$y=x^{2}+2 x+\mathrm{C}$

Differentiating both sides of this equation with respect to x, we get:

$y^{\prime}=\frac{d}{d x}\left(x^{2}+2 x+\mathrm{C}\right)$

$\Rightarrow y^{\prime}=2 x+2$

Substituting the value of $y^{\prime}$ in the given differential equation, we get:

L.H.S. $=y^{\prime}-2 x-2=2 x+2-2 x-2=0=$ R.H.S.

Hence, the given function is the solution of the corresponding differential equation.

Leave a comment


Click here to get exam-ready with eSaral

For making your preparation journey smoother of JEE, NEET and Class 8 to 10, grab our app now.

Download Now